Broadband Dual-Polarized Magnetoelectric Dipole Antenna With Compact Structure for 5G Base Station - Shihao Wu; Feng Shang (IEEE Access, 2023)
This paper presents a compact wideband dual-polarized magnetoelectric dipole antenna suitable for 5G base stations, which can cover 5G NR n77/78/79 band. The proposed antenna is configured with a cross ME dipole loaded with a rectangular slot, and two L-shaped feed lines are coplanar with the vertical patch, which makes the transverse size of the antenna more compact. The prototype size is $0.57\,\,λ _{min} × 0.57\,\,λ _{min}$ (length $× $ width). According to the measured results, the operating band of the antenna is 3.06-5.28 GHz, and the impedance bandwidth is 53.2% of −10 dB. In the whole frequency range, the isolation between ports is less than −22 dB. Furthermore, metal baffles around the ground are used to stabilize the radiation pattern and improve the front-to-back ratio, achieving gains greater than 8dBi in the frequency band. However, the half power beam width (HPBW) exceeds 65°±5° for base station applications. The antenna has the advantages of broadband, high front-to-back ratio and low cross-polarization, and can be used as a good candidate antenna for 5G commercial small base stations.